Passive immunization reduces murine cytomegalovirus-induced brain pathology in newborn mice - Cekinovic, Durdica; Golemac, Mijo; Pugel, Ester Pernjak; Tomac, Jelena; Cicin-Sain, Luka; Slavuljica, Irena; Bradford, Russell; Misch, Sonja; Winkler, Thomas; Mach, Michael; Britt, William J.; Jonjic, Stipan (Journal of Virology, 2008)
Human cytomegalovirus (HCMV) is the most frequent cause of congenital viral infections in humans and frequently leads to long-term central nervous system (CNS) abnormalities that include learning disabilities, microcephaly, and hearing loss. The pathogenesis of the CNS infection has not been fully elucidated and may arise as a result of direct damage of CMV-infected neurons or indirectly secondary to inflammatory response to infection. We used a recently established model of mouse CMV (MCMV) infection in newborn mice to analyze the contribution of humoral immunity to virus clearance from the brain. In brains of MCMV-infected newborn mice treated with immune serum, the titer of infectious virus was reduced below detection limit, whereas in the brains of mice receiving control (nonimmune) serum significant amounts of virus were recovered. Moreover, histopathological and immunohistological analyses revealed significantly less CNS inflammation in mice treated with immune serum. Treatment with MCMV-specific monoclonal antibodies also resulted in the reduction of virus titer in the brain. Recipients of control serum or irrelevant antibodies had more viral foci, marked mononuclear cell infiltrates, and prominent glial nodules in their brains than mice treated with immune serum or MCMV-specific antibodies. In conclusion, our data indicate that virus-specific antibodies have a protective role in the development of CNS pathology in MCMV-infected newborn mice, suggesting that antiviral antibodies may be an important component of protective immunological responses during CMV infection of the developing CNS. Copyright © 2008, American Society for Microbiology. All Rights Reserved.